Fostering Eco-Friendly Consumption: Advancing Sustainable Practices in Palestine - Sadeh, Hamdi (Technium Social Sciences Journal, 2025)
This research examines the promotion of eco-friendly consumption in Palestine, focusing on the distinct socio-political challenges and opportunities present in the region. Although awareness of environmental issues is growing among Palestinian consumers, significant barriers remain, including limited access to sustainable products and cultural attitudes that prioritize immediate economic benefits. The research emphasizes that consumer empowerment and engagement are crucial for overcoming these obstacles, highlighting the necessity of a collective responsibility shared among consumers, businesses, and policymakers to foster sustainable practices. To enhance eco-friendly consumption, the research proposes several strategies, including the improvement of consumer education through targeted outreach programs and the leveraging of technology to increase access to sustainable products. Importantly, it underscores the effectiveness of localized strategies, such as community-based educational initiatives, in addressing these barriers and cultivating a culture of sustainability that aligns with the socio-economic realities of Palestinian society. Furthermore, the findings highlight the critical importance of collaboration among various stakeholders; government entities, NGOs, the private sector, and local communities in creating a supportive environment for eco-friendly behaviors. This research aims to provide a comprehensive framework for advancing sustainable practices in Palestine, with implications that extend beyond the region, offering valuable insights for similar contexts grappling with socio-political challenges and environmental degradation.